A NOVEL ACENTRIC CHAR SULFATE INORGANIC-ORGANIC HYBRID FRAMEWORK: PHOTOLUMINESCENT, NLO AND SEMICONDUCTOR PROPERTIES - He, De-Yong; Chen, Wen-Tong (Journal of the Chilean Chemical Society, 2016)
A novel acentric char sulfate compound, [Cd(S2O7)(4,4’-bipyridine)(H2O)2]n (1), has been solvothermally synthesized and characterized by single-crystal X-ray diffraction method. Compound 1 is characterized by a three-dimensional (3-D) inorganic-organic hybrid framework structure. Solid-state photoluminescent spectra indicate that compound 1 displays a strong violet emission. The second-order nonlinear optical measurements reveal that compound 1 has modest powder SHG efficiency of about 0.02 times than that produced by a potassium dihydrogen phosphate (KDP) powder. Optical absorption spectrum discovers that the presence of an optical gap of 3.41 eV, suggesting that compound 1 is a wide bandgap semiconductor.